Slovenska jezikovna infrastruktura kot jezikovnopolitično vprašanje: potrebe in pričakovanja jezikovnih uporabnikov - Ledinek, Nina (Slavia Centralis, 2020)
Slovene language infrastructure as a language-policy issue: the needs and expectations of language usersThe article deals with Slovene language infrastructure as a language-policy issue. It presents an analysis of the current legal, financial and organizational arrangements in the field of language infrastructure, as well as key findings on users’ infrastructural needs, as identified on the basis of the analysis and interpretation of data from the survey conducted within the framework of the Language Policy of the Republic of Slovenia and the Needs of Users project.
Keywords: sociolinguistics; language policy; language status; language corpus; language resources; language technologies